Results of a collaborative study of the EDNAP group regarding the reproducibility and robustness of the Y-chromosome STRs DYS19, DYS389 I and II, DYS390 and DYS393 in a PCR pentaplex format. - Carracedo, A; Beckmann, A; Bengs, A; Brinkmann, B; Caglia, A; Capelli, C; Gill, P; Gusmão, L; Hagelberg, C; Hohoff, C; Hoste, B; Kihlgren, A; et al. (2001)
A collaborative exercise was carried out by the European DNA Profiling Group (EDNAP) in the frame work of the STADNAP program, i.e. standardization of DNA profiling in Europe, in order to evaluate the performance of a Y-chromosome STR pentaplex, which includes the loci DYS19, DYS389 I and II, DYS390 and DYS393 and to determine whether uniformity of results could be achieved among different European laboratories. Laboratories were asked to analyze the five Y-STRs using singleplex and multiplex conditions in three bloodstains and one mixed stain (95% female and 5% male). All the laboratories reported the same results even for the mixed stain included in the exercise. This demonstrates the reproducibility and robustness of Y-chromosome STR typing even with multiplex formats and proves the usefulness of Y-STR systems for analyzing mixed stains with a male component.A total of 930 male samples from 10 different populations from Europe were also analysed for all the loci included in the pentaplex. Eight of these ten populations also included haplotype data. As for single gene analysis, haplotype diversity was higher in Germany and Italy and lower in Western European countries and Finland. Pairwise haplotype analysis shows the Finnish departure from the rest of the populations and a relatively homogeneity in the other European populations with F(ST) estimates lower than 0.05.UPGMA analysis shows an association of Western European population (Ireland, UK, Portugal and Galicia) on the one hand and central European populations on the other.